Detección inmunoenzimática de la toxina de la bacteria Clostridium tetani: una alternativa a las pruebas biológicas con ratones - Chaves, Fernando (Universidad de Costa Rica, 2006)
Cell-free extracts from 20 strains of Clostridium tetani isolated from soil samples, were tested for tetanus toxin production using an enzyme immunoassay. All the extracts were classified as positive for the toxin presence, and eight of them showed absorbance values corresponding to tetanus toxin concentrations between 3.2 and 88 ng/ml; thus, they fell within the linear absorbance range (0.135-0.317). All dilutions of toxin used to obtain the calibration curve (0.0071 to 1.1 ng) were lethal for mice.